Analysis of Rain Intensity Calculation Based on Rainfall Data from the Rain Station in Amuntai City, Hulu Sungai Utara District - Suwaji; Anisari, Rezky (PT FORMOSA CENDEKIA GLOBAL, 2024)
Flood management in South Kalimantan has been crucial in addressing the devastating floods that occurred in 2021. The event, which spanned around 4000 km2, was exacerbated by land cover changes and continuous rainfall. Understanding the factors contributing to flooding is essential for developing effective mitigation and management measures. Utilizing methodologies like calculating rainfall intensity, analyzing rainfall patterns, and employing models like IDF curves and nomographs can enhance flood prevention efforts and develop more effective strategies to mitigate the impact of floods. This research aims to calculate the flood debit plan using an empirical method. This study employs the Library Study Method and conducts a rainfall analysis to determine the Flood Debit Value of the State River Flow Area Plan (DAS), utilizing the Rational Method, the Der Weduwen Method, and the Haspers Method. The highest annual effective rainfall data for the study area was found for 2.5, 10, 25, and 50 years. The Flood Debit Value of the Plan (Qbr) was found using the following logical methods: 419.14 m3/s, 533.75 m3/s, 562.75 m2/s, 603.32 m3/s, and 649.62 m3/s. The rational method yielded the largest flood debit plan, which can serve as guidelines or a reference for future planning of water buildings for flood control in the State River. This is based on the analysis of the calculation of flood debit plans based on the maximum annual rainfall and effective rainfall of the area of river flow (DAS) in the State River streets, Pandan river district, Pandan (Alabio), Hulu Sungai Utara